2022
DOI: 10.1002/cre2.537
|View full text |Cite
|
Sign up to set email alerts
|

Active MMP‐8 point‐of‐care (PoC)/chairside enzyme‐test as an adjunctive tool for early and real‐time diagnosis of peri‐implantitis

Abstract: Objective The aim of this study was to investigate the utility of the active matrix metalloproteinase (aMMP‐8)‐point‐of‐care (PoC) test as a quantitative real‐time chair‐side diagnostic tool for peri‐implant diagnosis, as well as assess the potentially developing and ongoing risk relative to the traditional clinical methods. Background Current peri‐implant and periodontal disease diagnoses rely on clinical and radiological examinations. This case‐control study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The systematic literature review yielded a total of seven papers for analysis. Of these, 213 articles were excluded because smoking status was not reported [ 9 , 13 , 33 ] or because they entailed a topic unrelated to the study question [ 18 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic literature review yielded a total of seven papers for analysis. Of these, 213 articles were excluded because smoking status was not reported [ 9 , 13 , 33 ] or because they entailed a topic unrelated to the study question [ 18 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the MMPs, MMP-8 and MMP-9 are in the spotlight as biomarkers for periodontal disease. A kit that can test for MMP-8 in 5 min in an office has been developed [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with previous studies that have shown a direct correlation between active MMP-8 levels and periodontal/peri-implant clinical parameters, 10,13,15,17,18 while this strong correlation was not observed between the levels of the total enzyme (both active and latent forms). 19 As discussed earlier, to maintain periodontal and periimplant health, it is crucial to establish collagen balance. The presence of collagen degradation is not feasible to be detected with clinical examination and radiographs, which are the regular assessments of the peri-implant tissues at the dental settings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the incorporation of validated biomarkers will improve the diagnostic accuracy and assessment of the stage and grade of the new periodontitis classification system by Tonetti et al [100] and recent data indicate that the aMMP-8 mouthrinse test can provide this capability in periodontitis as well as periimplantitis [21,25,28,101,102]. With this background, we now present a modified new classification table with aMMP-8 implemented as the needed biomarker for periodontitis and peri-implantitis (Table 1).…”
Section: Ammp-8 As Part Of a Screening Strategy Formentioning
confidence: 99%
“…This fact is supported by the present data, as the subgroup of participants with aMMP-8 levels above 20 ng/mL demonstrated statistically significant differences in clinical parameters of periodontal and peri-implant diseases when compared to subjects with PerioSafe R -and ImplantSafe R ORALyzer R aMMP-8 values below this threshold. The aMMP-8 PoCT-test values < 20 ng/mL can be regarded as biomarkers of periodontal and peri-implant health [21,25,28,101,102].…”
Section: Ammp-8 As Part Of a Screening Strategy Formentioning
confidence: 99%